Solid-state battery cell with intercalation structure and method of making the same
Patent Information
- Application Number
- CN202110359752.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-04-02
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2041-04-02
AI Technical Summary
[0005]本发明的目的是提供一种具有互嵌结构的固态电池电芯,其能够克服目前的固态电池封装中平行结构导致的电极与固态电解质接触面积不足的问题,并且还能够克服循环后电极体积效应引起结构破坏的问题
Smart Images

Figure CN115189012B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of energy storage technology. Specifically, this invention relates to a solid-state battery cell with an interlocking structure and its preparation method. Background Technology
[0002] Solid-state batteries are widely considered the next-generation battery technology due to their high safety and high specific energy. Because solid-state batteries use a solid electrolyte instead of the electrolyte found in lithium-ion batteries, the positive electrode material and the electrolyte are connected via a solid-solid interface. When using positive and negative electrode materials with high volume effects, the low solid-solid interface contact area and interface separation directly affect the battery's electrical performance.
[0003] Meanwhile, during battery assembly, the dense pressing process can easily lead to permeation at the solid-solid interface, causing deformation of low Young's modulus materials such as the electrolyte. In simple parallel-structure solid-state batteries, this large-planar, ultra-thin electrolyte layer structure is highly prone to internal short circuits.
[0004] There is an urgent need for a cell structure that allows for large contact area between the electrode and the solid electrolyte, minimizes internal short circuits, and allows for free combination in series and parallel connections. Summary of the Invention
[0005] The purpose of this invention is to provide a solid-state battery cell with an interlocking structure, which overcomes the problem of insufficient contact area between the electrodes and the solid electrolyte caused by the parallel structure in current solid-state battery packaging, and also overcomes the problem of structural damage caused by electrode volume effects after cycling. The solid-state battery cell provided by this invention divides the cell into a large number of tiny units, which can eliminate a small number of defective units during manufacturing and can be freely combined in series and parallel according to the design voltage requirements. Another purpose of this invention is to provide a method for manufacturing a solid-state battery cell with an interlocking structure.
[0006] The above-mentioned objective of the present invention is achieved through the following technical solution.
[0007] In a first aspect, the present invention provides a solid-state battery cell with an interlocking structure, comprising a positive electrode, a negative electrode, and a solid electrolyte layer, wherein...
[0008] The positive electrode includes a positive electrode current collector and a positive electrode material loaded on the positive electrode current collector, wherein the surface of the positive electrode material has at least one pit;
[0009] The solid electrolyte layer adheres to the entire surface of the pit.
[0010] The negative electrode includes at least one negative electrode region and a negative electrode current collector electrically connected to the negative electrode region, wherein the negative electrode region is formed by a negative electrode material filled with pits to which a solid electrolyte layer is attached, and the negative electrode current collector is disposed on the surface of the negative electrode region and electrically connected to the negative electrode region.
[0011] Preferably, in the solid-state battery cell with an interlocking structure according to the present invention, an electrically insulating material layer is disposed on the surface of the positive electrode material to electrically insulate the positive electrode material from the negative electrode current collector. In the present invention, "disposing of an electrically insulating material layer on the surface of the positive electrode material" means that the electrically insulating material layer covers the surface of the positive electrode material or covers and extends beyond the surface of the positive electrode material.
[0012] Preferably, in the solid-state battery cell with interlocking structure of the present invention, the electrical insulating material layer has a through hole at a position corresponding to the negative electrode region, and the negative electrode current collector has a protrusion matching the through hole to penetrate the electrical insulating material layer and be electrically connected to the negative electrode region.
[0013] Preferably, in the solid-state battery cell with interlocking structure described in this invention, the shape of the recess is cylindrical, pyramidal, truncated conical, or prismatic.
[0014] In a specific embodiment of the present invention, the shape of the recess is an inverted truncated cone.
[0015] Preferably, in the solid-state battery cell with an interlocking structure described in this invention, the pits are arranged in an array.
[0016] Preferably, in the solid-state battery cell with an interlocking structure according to the present invention, the array arrangement is carried out in the following manner:
[0017] The pits are arranged in separate rows along a first direction and spaced apart within each row in a second direction, wherein the first and second directions are perpendicular to each other and the plane formed by the first and second directions is parallel to the upper surface of the positive electrode material.
[0018] Preferably, in the solid-state battery cell with interlocking structure described in this invention, the size of the pit is 100-20000μm, more preferably 100-9000μm.
[0019] Preferably, in the solid-state battery cell with interlocking structure described in this invention, the thickness of the solid electrolyte layer is 1-100 μm.
[0020] Preferably, in the solid-state battery cell with interlocking structure described in this invention, the thickness of the negative electrode current collector is 1-50 μm, more preferably 1-20 μm.
[0021] Secondly, the present invention provides a method for preparing a solid-state battery cell with an interlocking structure, comprising the following steps:
[0022] (1) Load the positive electrode material onto the surface of the positive electrode current collector, and form at least one pit on the surface of the positive electrode material by pressing;
[0023] (2) A solid electrolyte layer is attached to the entire surface of the pit;
[0024] (3) Fill the pits with the solid electrolyte layer with negative electrode material to form a negative electrode region;
[0025] (4) Connect the negative electrode current collector to the negative electrode region electrically;
[0026] (5) Optionally, prior to step (4), an electrically insulating material layer is formed on the surface of the positive electrode material.
[0027] Thirdly, the present invention provides a solid-state battery cell with a series structure, which is composed of at least two cell sub-units connected in series via connecting terminals (see [link]). Figure 3 The cell subunit includes the solid-state battery cell with an inter-insertion structure of the present invention.
[0028] In a specific embodiment of the present invention, the negative electrode current collector can be layered and encapsulated at the top to form a single-layer cell structure, or it can be stacked to realize that each single-layer cell is connected in series with each other in a solid-state battery.
[0029] In a specific embodiment of the present invention, an insulating, water- and oxygen-barrier thin film is used to encapsulate a solid-state battery cell by hot pressing to form a solid-state battery.
[0030] In a specific embodiment of the present invention, the surface of the positive current collector needs to be cleaned before use.
[0031] In a specific embodiment of the present invention, a positive electrode material is loaded onto the surface of a positive electrode current collector with a back structure, and an array of inverted truncated conical pits is prepared by cold pressing.
[0032] In a specific embodiment of the invention, a liquid electrolyte is attached to a recess in the shape of an inverted truncated cone using a mask template, or by deposition. The electrolyte is then shaped using a mold and heat-treated to form the desired solid electrolyte.
[0033] In a specific embodiment of the present invention, a negative electrode slurry is filled inside an inverted truncated cone-shaped solid electrolyte interface. The negative electrode slurry is injected by cold rolling or melting to form a negative electrode material. The interface between the electrolyte and the negative electrode material may or may not be treated. Preferably, a metal mixed conductivity layer is used for modification.
[0034] In specific embodiments of the present invention, conventional methods in the art can be used to prepare the desired negative electrode current collector, such as the method disclosed in patent application 201410440238.6.
[0035] In a specific embodiment of the present invention, the negative electrode current collector is cold-pressed out, and the single-layer cells are stacked into groups to realize internal stacking of the battery, thereby realizing internal series connection of the battery.
[0036] In a specific embodiment of the present invention, positive and negative electrode tabs are led out from the side of the battery cell, and then transferred and heat-sealed.
[0037] The present invention has the following beneficial effects:
[0038] On the one hand, the solid-state battery cell of the present invention has the advantage of a large contact area between the electrode and the solid electrolyte. On the other hand, the solid-state battery cell of the present invention is not prone to short circuits and can also overcome the problem of structural damage caused by electrode volume effect after cycling. In addition, the solid-state battery cell provided by the present invention divides the cell into a huge number of tiny units, which can eliminate a small number of defective units during manufacturing, and according to the design voltage requirements, series connection between the various cell sub-units can be realized by adding connection terminals between each cell sub-unit (see [link]). Figure 3 The solid-state battery cell with an interlocking structure provided by this invention is actually a parallel connection of cell structures (see...). Figure 1 As can be seen, the solid-state battery cell with an interlocking structure provided by this invention can achieve free series and parallel connection of the cell structure. Attached Figure Description
[0039] The embodiments of the present invention will now be described in detail with reference to the accompanying drawings, wherein:
[0040] Figure 1 This is a side cross-sectional view of a solid-state battery cell according to a specific embodiment of the present invention;
[0041] Figure 2 A top cross-sectional view of a solid-state battery cell without a negative electrode current collector, according to a specific embodiment of the present invention;
[0042] Figure 3 This is a side cross-sectional view of a series-connected battery cell sub-unit according to a specific embodiment of the present invention. Detailed Implementation
[0043] The present invention will be further described in detail below with reference to specific embodiments. The embodiments given are only for illustrating the present invention and are not intended to limit the scope of the present invention.
[0044] Example 1
[0045] (1) Preparation of positive electrode
[0046] A 12 μm thick aluminum foil was used as the positive electrode current collector. The current collector was then ultrasonicated for 30 min with deionized water and ethanol, respectively, and subsequently dried under vacuum at 120 °C. A mixture of LCO positive electrode active material, LGPS sulfide electrolyte, carbon nanotubes, and PVDF in a mass ratio of 5:3:1:1 was ball-milled at 400 r / min under an inert N2 atmosphere for 3 h, and then dispersed in anhydrous NMP to form a mixture with a solid content of 60 wt%. This mixture was coated onto one surface of the positive electrode current collector to form an 1800 μm thick positive electrode precursor. The precursor was then compacted under low vacuum (<100 Pa) using a frustum-shaped metal mold with a depth of 1250 μm to shape the precursor, and finally cold-rolled at 50 MPa for 15 min to form the desired positive electrode.
[0047] (2) Preparation of solid electrolyte layer
[0048] LGPS and LPS sulfide solid electrolytes (mixed in a 1:1 weight ratio) were ball-milled with PTFE binder at 300 r / min under an inert N2 atmosphere for 2 h, with the PTFE binder accounting for 2 wt% of the total mixture. After mixing, the mixture was dispersed in anhydrous cyclohexane to form a liquid solution with a solid content of 80% by mass. A mask was placed over the surface of the positive electrode to cover the non-inverted truncated conical region, and the liquid solution was sprayed into the pits to form a 200 μm thick liquid electrolyte. Then, the liquid electrolyte was compacted using a coaxial frustum-shaped metal mold under a low vacuum (<100 Pa) environment to conform to the pits of the inverted truncated cone of the positive electrode. Cold rolling was then performed at 10 MPa for 5 min, followed by hot pressing at 200 °C for 5 min to form a crystallized solid electrolyte layer structure.
[0049] (3) Anode preparation
[0050] A 1 μm gold layer was deposited at the solid electrolyte interface using magnetron sputtering to form a mixed ionic conductivity layer. Lithium metal was heated to 180 °C in an inert Ar2 atmosphere to melt it, and then injected into the pores using a microneedle, with the filled negative electrode and positive electrode plateau regions being flush.
[0051] (4) Preparation of negative electrode current collector
[0052] A flexible negative electrode bilayer current collector was formed using a 20 μm thick composite flexible FPC film with an annular insulating layer and an Fe metal conductive layer. This negative electrode bilayer current collector was then placed on top of a planar negative electrode and cold-pressed at 10 MPa for 5 min. A 30 μm thick polyimide film with positive and negative electrode tabs was then cold-rolled with the positive and negative electrode current collectors respectively, thus completing the fabrication of a monolithic solid-state battery cell.
[0053] (5) Solid-state battery fabrication
[0054] Repeat the single-layer cell fabrication steps described above, transferring and stacking layers on the outside of the negative electrode sheet to form series connections within the cell. Align and stack the multi-layered cell, weld the positive and negative electrode tabs at the cell edges, pre-encapsulate using an aluminum-plastic film (edge temperature 150°C), and then place the fabricated solid-state battery cell into a sealed bag under vacuum. Finally, hot-press it at 600 MPa and 170°C for 30 seconds using a hot isostatic press to complete the solid-state battery fabrication.
[0055] Comparative Example 1
[0056] (1) Preparation of positive electrode
[0057] A mixture of LCO ternary cathode material, LGPS sulfide electrolyte, Super P conductive carbon, PTFE, and graphene in a mass ratio of 4.5:3:1.5:0.5:0.5 was ball-milled at 300 r / min under an inert N2 atmosphere for 1 h, and then dispersed in anhydrous cyclohexane to form a mixture with a solid content of 60% by mass. This mixture was coated onto the surface of a standard cathode current collector to form a 120 μm thick cathode precursor, which was then vacuum-dried at 120 °C for 6 h. The cathode precursor was then compacted into a planar electrode using a flat mold under a low vacuum (<100 Pa). It was then cold-pressed at 10 MPa for 5 min, followed by hot-pressing at 150 °C for 10 min, and then cold-pressed again at 400 MPa using an isostatic press for 60 s, after which the pressure was removed.
[0058] (2) Preparation of solid electrolyte layer
[0059] LPS sulfide solid electrolyte was mixed with 2 wt% PTFE binder and ball-milled at 300 r / min in an inert N2 atmosphere for 1 h. The mixture was then dispersed in anhydrous cyclohexane to form a liquid solution with 80% solid content by mass. This solution was sprayed onto the surface of the prepared planar cathode to form a 20 μm thick liquid electrolyte. The solution was then compacted under a low vacuum (<100 Pa), followed by cold rolling at 10 MPa for 5 min, and then hot-pressed at 160 °C for 10 min to form a solid electrolyte layer structure. Nanosecond infrared laser drying was used to rapidly and locally heat only the electrolyte region, raising the electrolyte temperature to 460 °C to enhance crystallinity.
[0060] (3) Preparation of negative electrode
[0061] Lithium metal was mixed with 2 wt% Ag at 180 °C to form a liquid metal, which was then uniformly coated onto a stainless steel substrate. After cooling, the negative electrode was separated. The lithium metal negative electrode was thinned to 100 μm using a roller press. A 30 nm high-conductivity amorphous carbon layer was deposited on the 100 μm thick lithium metal surface by ion sputtering as a conductive layer. The prepared negative electrode mixed-conductivity layer was then brought into contact with the prepared solid electrolyte layer to form a planar stacked structure.
[0062] (4) Preparation of negative electrode current collector
[0063] A flexible negative electrode bilayer current collector was formed using a 20 μm thick composite flexible FPC film with an annular insulating layer and an Fe metal conductive layer. This negative electrode bilayer current collector was then placed on top of a planar negative electrode and cold-pressed at 10 MPa for 5 min. Next, a 30 μm thick polyimide film with positive and negative electrode tabs was cold-rolled with the positive and negative electrode current collectors respectively, thus completing the fabrication of a monolithic solid-state battery cell.
[0064] (5) Solid-state battery fabrication
[0065] Two prepared cell layers are aligned and stacked. The prepared solid-state battery cell film is placed in a polyimide film sealed bag and then hot-pressed at 400 MPa and 200°C for 30 seconds. Then, excess polyimide film on the outer edge tab is removed using a laser to form a solid-state battery.
[0066] Example 2
[0067] The electrochemical performance of the prepared nested array solid-state battery and parallel structure battery was tested using a battery testing system from Wuhan Landian Electronics Co., Ltd. The test temperature was 60℃, and the test voltage was 3.0–4.3V vsLi. + / Li, tested at rates of 0.05C and 0.1C, with nominal capacity calculated at 145mAh / g. The specific capacity of the entire battery is calculated based on the mass of the LCO cathode active material.
[0068] Table 1 Performance test results of Example 1 and Comparative Example 1
[0069]
[0070] As shown in Table 1 above, the electrochemical performance of solid-state batteries fabricated using a frustum array structure is significantly improved due to the high contact area between the electrodes and the solid electrolyte. Firstly, the discharge capacity at 0.05C and 0.1C is higher; secondly, the capacity retention at 50 cycles at 0.1C increases from approximately 70% to approximately 96%. The main reason for this performance improvement is the significantly increased contact area between the electrodes and the solid electrolyte through the nested configuration, thereby enhancing capacity release. Simultaneously, the cavity structure mitigates material failure caused by volume expansion, thus improving cycle stability. This invention solves the problem of capacity decay in solid-state batteries caused by poor interfacial contact and large volume changes, and has positive implications for practical applications.
Claims
1. A solid-state battery cell with an intercalation structure, comprising a positive electrode, a negative electrode, and a solid electrolyte layer, wherein, The positive electrode includes a positive electrode current collector and a positive electrode material loaded on the positive electrode current collector, wherein one side surface of the positive electrode material has at least one pit recessed into the interior of the positive electrode material; The solid electrolyte layer is attached to the entire surface of the pit; The negative electrode includes at least one negative electrode region and a negative electrode current collector electrically connected to the negative electrode region, wherein the negative electrode region is formed by a negative electrode material filled with pits to which a solid electrolyte layer is attached, and the negative electrode current collector is disposed on the surface of the negative electrode region and electrically connected to the negative electrode region. An electrically insulating material layer is disposed on the surface of the positive electrode material to make the positive electrode material electrically insulated from the negative electrode current collector; the electrically insulating material layer has a through hole at a position corresponding to the negative electrode region, and the negative electrode current collector has a protrusion that matches the through hole to penetrate the electrically insulating material layer and be electrically connected to the negative electrode region. The method for preparing the solid-state battery cell with the interlocking structure includes the following steps: (1) Load the positive electrode material onto the surface of the positive electrode current collector, and form at least one pit on the surface of the positive electrode material by pressing; (2) A solid electrolyte layer is attached to the entire surface of the pit; (3) Fill the pits with the solid electrolyte layer with the negative electrode material to form the negative electrode region; (4) Connect the negative electrode current collector to the negative electrode region electrically; (5) Before step (4), an electrically insulating material layer is formed on the surface of the positive electrode material.
2. The solid-state battery cell with an interlocking structure according to claim 1, wherein, The shape of the pit is cylindrical, pyramidal, truncated conical, or prismatic.
3. The solid-state battery cell with an interlocking structure according to claim 1, wherein, The pits are arranged in an array.
4. The solid-state battery cell with an interlocking structure according to claim 3, wherein, The array arrangement is performed in the following manner: The pits are arranged in separate rows along a first direction and spaced apart within each row in a second direction, wherein the first and second directions are perpendicular to each other and the plane formed by the first and second directions is parallel to the upper surface of the positive electrode material.
5. The solid-state battery cell with an interlocking structure according to claim 1, wherein, The thickness of the solid electrolyte layer is 1-100 μm.
6. The solid-state battery cell with an interlocking structure according to claim 1, wherein, The thickness of the negative electrode current collector is 1-50 μm.
7. The solid-state battery cell with an interlocking structure according to claim 6, wherein, The thickness of the negative electrode current collector is 1-20 μm.
8. A solid-state battery cell with a series structure, comprising at least two cell sub-units connected in series via connecting terminals, wherein the cell sub-units include any one of claims 1-7 solid-state battery cells with an interlocking structure.
Citation Information
Patent Citations
Rigid flexible pcb and method for manufacturing the same
CN104427754A
Manufacturing method and manufacturing apparatus of battery
JP2014006965A